2002
DOI: 10.1530/eje.0.1470795
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of CYP11B1 and CYP11B2 expression in aldosterone-producing adenomas

Abstract: Background: The presence and pathophysiological role of CYP11B1 (11b-hydroxylase) gene in the zona glomerulosa of human adrenal cortex is still controversial. Methods: In order to specifically quantify CYP11B1, CYP11B2 (aldosterone synthase) and CYP17(17a-hydroxylase) mRNA levels, we developed a real-time RT-PCR assay and examined the expression in a series of adrenal tissues, including six normal adrenals from patients adrenalectomized for renal cancer and twelve aldosterone-producing adenomas (APA) from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 32 publications
(25 reference statements)
8
47
2
1
Order By: Relevance
“…32 Most unexpectedly, however, different authors found subsets of tumors with highly heterogeneous expression of CYP11B2 either increased, unchanged, or decreased compared with control adrenal tissue. 34,36 A very recent transcriptome study further demonstrated the tumor heterogeneity of CYP11B2 expression and the correlation of high versus low CYP17A1 expression in APA with morphological features, that is, adenomas composed of zona fasciculata-like cells versus tumors composed of ZG-like cells, respectively.…”
Section: From Physiological To Pathological Aldosterone Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Most unexpectedly, however, different authors found subsets of tumors with highly heterogeneous expression of CYP11B2 either increased, unchanged, or decreased compared with control adrenal tissue. 34,36 A very recent transcriptome study further demonstrated the tumor heterogeneity of CYP11B2 expression and the correlation of high versus low CYP17A1 expression in APA with morphological features, that is, adenomas composed of zona fasciculata-like cells versus tumors composed of ZG-like cells, respectively.…”
Section: From Physiological To Pathological Aldosterone Productionmentioning
confidence: 99%
“…Using various techniques, several studies have thus reported increased expression of CYP11B2 in APA compared with normal adrenals or peritumoral adjacent cortex [31][32][33][34][35][36] (throughout this review, "adjacent cortex" refers to the entire cortex of an adrenal gland harboring an APA). In addition to CYP11B2, expression of CYP21A2 (coding for steroid 21-hydroxylase, responsible for the conversion of progesterone into 11-deoxycorticosterone) has been found to be consistently increased in APA, 37,38 whereas mRNA levels of CYP11B1 were decreased, 32,38 and there were no changes in CYP11A1 expression. 36 Remarkably enough, these studies also revealed a relative heterogeneity in terms of gene expression.…”
Section: From Physiological To Pathological Aldosterone Productionmentioning
confidence: 99%
“…1D). Surprisingly, the level of enzyme detected in skin was comparable to the adrenal gland (51). Protein extracts from lymphocytes, which do not express CYP11B1 (52), were used as a negative control, and no signal was detected.…”
Section: Cyp11b1 An Enzyme Responsible For the Finalmentioning
confidence: 99%
“…Quando restos adrenais estão presentes na rede testicular, pequenas elevações ou elevações intermitentes do ACTH e da angiotensina II (AII) podem induzir a proliferação dessas células no testículo. Sugere-se que a AII seja um importante fator na estimulação do crescimento adrenal (8,9). Além disso, o controle hormonal inadequado, com elevações mais pronunciadas do ACTH, poderia acelerar esse processo.…”
Section: Relato Do Casounclassified